2022
DOI: 10.3389/fncom.2022.986591
|View full text |Cite
|
Sign up to set email alerts
|

Big data analytics frameworks for the influence of gut microbiota on the development of tic disorder

Abstract: The association between gut microbiota and psychiatric disorders has received increasing research attention. Meanwhile, big data analysis has been utilized in many filed including business, human healthcare analysis, etc. The primary objective of this article was to provide insights into Big Data Analytics (BDA) to clarify the association between gut microbiota and TD (Tic disorder). Specifically, we investigated the recent studies related to gut microbiota composition differences in patients with TD compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…16,17 Alterations in microbiome abundance may play a critical role in the development or manifestation of OCD for several reasons. First, an altered microbiome has been implicated in various neuropsychiatric disorders, such as anxiety 18 and tic 19 disorders, commonly associated with OCD. Two pilot studies suggest a gut microbial imbalance in OCD have been recently reported.…”
mentioning
confidence: 99%
“…16,17 Alterations in microbiome abundance may play a critical role in the development or manifestation of OCD for several reasons. First, an altered microbiome has been implicated in various neuropsychiatric disorders, such as anxiety 18 and tic 19 disorders, commonly associated with OCD. Two pilot studies suggest a gut microbial imbalance in OCD have been recently reported.…”
mentioning
confidence: 99%